Validity of The Electronic Enrichment Book "Sitinjau Lauik from the Perspective of Physics" - Virji, Julia; Desnita, Desnita; Hidayati, Hidayati; Riyasni, Selma (Indo-MathEdu Intellectuals Journal, 2025)
Education is basically an investment in human resource development that is indispensable in society. One of the important skills that must be possessed in the era of globalization is the ability to solve problems. Students are considered to be able to solve problems if they are able to understand, choose strategies, and then apply them in problem solving. But in reality, students' problem-solving skills are still low. Therefore, learning resources are needed that can train problem-solving skills. One of the learning resources that can be developed is electronic enrichment books. This study uses the R&D research method. The model used in this study is the 4-D model. The population in this study is 78 students in grade XI Phase F for the 2024/2025 school year. The sample of this study was carried out by random sampling with the research subject of physics lecturers of FMIPA UNP with a total of 3 lecturers. Based on the results of the research of the electronic enrichment book entitled "Sitinjau Lauik from the Perspective of Physics" which was developed, a validity score was obtained from 3 experts with an average score of 0.82 with very valid criteria. Based on this, electronic enrichment books that are developed and arranged in such a way can be used as a physics learning resource that trains the problem-solving skills of high school students.